Uzbekistan and Kazakhstan : A Tale of Two Transition Paths - Alam, Asad; Banerji, Arup (World Bank, Washington, DC, 2014)
Uzbekistan adopted a cautious, gradual approach to market reform. Kazakhstan followed a more aggressive strategy. But while Kazakhstan may have achieved a better policy environment, its economic performance has not been better than Uzbekistan's. The authors examine the interplay between policies, institutions, and initial conditions, to examine several competing, and complementary hypotheses about why the paths the two Central Asian countries took, may have led to different economic outcomes. One possibility is that missing pieces in reform - especially deficiencies in the competitive environment - in combination with a rapidly diminishing role for the state, may have limited the gains from the policy reforms in Kazakhstan.